Marketing management : strategies and programs - Guiltinan, Joseph P.; Paul, Gordon W. (New York : McGraw-Hill, 1982)
The book covers most of the basic concepts of marketing from a decision-making perspective rather than from a descriptive perspective, although in a amore sophisticated version. It focuses more on the middle management marketing decisions.
Includes index.
kjo 16/01/2-19
Loans
Keywords: Marketing---Management